1975
DOI: 10.1007/bf00223836
|View full text |Cite
|
Sign up to set email alerts
|

Comparative ultrastructure of cerebrospinal fluid-contacting neurons and pinealocytes

Abstract: The pinealocytes of fishes, amphibians, reptiles, birds and mammals have been compared with cerebrospinal fluid (CSF) contacting neurons. We found that the intraventricular dendrite terminal of the latter resembles the pinealocytic inner segment and that the atypical cilium (9x2+0 tubules) of the CSF contacting neurons is analogous with the outer segment of the pinealocytes, even though the outer segment bears photoreceptor lamellae in lower vertebrates. Regular, but small-sized photoreceptor outer segments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
37
0

Year Published

1977
1977
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 45 publications
2
37
0
Order By: Relevance
“…Recent studies on the liquor contacting neurons have revealed their characteristic apical structures and their synaptic connections (VIGH and VIGH-TEICHMANN, 1973;VIGH-TEICHMANN and VIGH, 1974). The morphology of these cells strongly supports the view that they are chemoreceptors of the cerebrospinal liquor, although this has not been evidenced by physiological experiments.…”
mentioning
confidence: 99%
“…Recent studies on the liquor contacting neurons have revealed their characteristic apical structures and their synaptic connections (VIGH and VIGH-TEICHMANN, 1973;VIGH-TEICHMANN and VIGH, 1974). The morphology of these cells strongly supports the view that they are chemoreceptors of the cerebrospinal liquor, although this has not been evidenced by physiological experiments.…”
mentioning
confidence: 99%
“…Contrary to the general view that the mammalian pinealocytes are simple glandular cells, they actually exhibit structures typical of a photosensory cell by their 9+0-type cilia and innersegment-like processes (WOLFS, 1965;CLABOUGH, 1971;ZIMMERMANN and Tso, 1975;MOLLER, 1986), by their synaptic ribbons found in about 30 mammalian species (MCNULTY and Fox, 1922) and by their axonal processes forming synapses on secondary pineal neurons in some species (VIGH and VIGH-TEICHMANN, 1975;VIGH et al, 1975VIGH et al, , 1986bVIGH-TEICHMANN, 1991), and further by the presence of substances known for their role in retinal phototransduction (KALSOW and WACKER;1977;VIGH-TEICHMANN et al, 1986;ABE and SHINOHARA, 1990;PALCZEWSKI et al, 1990;VIGH-TEICHMANN and VIGH, 1992;LOLLEY et al, 1992).…”
Section: Discussionmentioning
confidence: 88%
“…This neurosensory character may explain the ability to concentrate calcium ions (see below). It also raises the question of whether the pinealocytes of all mammalian species have indeed lost their direct photosensitivity (VIGH and VIGH-TEICHMANN, 1989a;VIGH-TEICHMANN and VIGH, 1992). Like insectivores, the mustelids are ancient carnivores, representing a phylogenetically old group of mammals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is probable that ENT directly exerts an effect upon the neurons in the CNS, since it is suggested that ENT is an endogenous agonist of Ca channels (YANAGISAWA et al, 1988a, b), which play a significant role in neural conduction as well as in vascular smooth muscle contraction. On the other hand, since peptides can be rapidly distributed into the brain interstitial space of the circumventricular organs, i.e., about six small regions around the ventricles which lack a blood-brain barrier (WEINDL, 1973), and the cerebrospinal fluid (CSF) is capable of transmitting information from one area of the brain to another by virture of special nerve cells with processes straight into the CSF (VIGH and VIGH-TEICHMANN, 1973), it is probable that i.c.v. injected ENT is capable of influencing the neurons in the CNS.…”
Section: Discussionmentioning
confidence: 99%